OKUL YÖNETİCİLERİNİN DEĞERLERLE YÖNETİM KAVRAMINA İLİŞKİN ALGILARI - Demirtaş, Zülfü; Kılıç, Mehmet Fatih (Fırat University, 2015)
Bu araştırma ortaöğretim okul yöneticilerinin değerlerle yönetime ilişkin algılarını belirlemek amacıyla nitel araştırma yaklaşımı ile içerik analizi yapılarak gerçekleştirilmiştir. Bu amaç doğrultusunda, 2011-2012 eğitim-öğretim yılında, Elazığ ili merkezinde farklı türlerdeki 23 ortaöğretim kurumun 44 yöneticisi, bu çalışmadaki araştırma grubu olarak ele alınmıştır.Çalışmada yönetici görüşleri yarı yapılandırılmış görüşme yöntemi ile alınmış, veriler niteliksel analiz yöntemiyle çözümlenmiştir. Okul yöneticilerinin değerlerle yönetime ilişkin algıları altı tema altında toplanmaktadır. Bu temalar sırasıyla; milli ve manevi değerler, değerlere öncelik verilmesi, toplumsal değerler, eğitime öncelik verilmesi, etkili yönetim ve kurum kültürüdür. Okul yöneticileri, değerlerin, özellikle yönetim ve eğitim açısından vazgeçilmez bir temel oluşturduğuna vurgu yapmıştır. Okul yöneticilerine göre; yöneticiler değerleri özümsemeli ve etkili iletişim kurama becerisine sahip olmalıdır. Değerlerle yönetimin olumlu okul iklimi oluşturmada, eğitsel amaçlara ulaşmada, okulun etkililiğini artırmada önemli roller oynayabileceği düşünülmektedir.

This research has been carried out with qualitative research method and content analysis to identify the perception of secondary school principals of value based management. For this purpose in 2011-2012 academic year forty four principals of twenty three high schools of varied types in Elazığ city centre were interviewed. In the study principals’ views were collected through semi-structured interview method and datum were resolved with qualitative analysis methods. As a result it can be concluded that; principals consider value based management both as an objective for schools that are primarily expected to form personality and transfer values and also as a tool to reach this aim in terms of training and management, and at the same time value based management is considered to give primary importance to social, national and moral values in management. Principals underline that values constitute an indispensable basis especially for management and education. According to the school principals; managers should internalize values, they should have effective communication skills and value based management’s role in the enhancement of productivity of every activity in educational institutions and reach the objectives created in order to form a positive school climate is heeded a great deal by principles.
The Perceptions of School Administrators About Concept of Value Based Management